2009
DOI: 10.1177/0143624408099175
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for post-occupancy evaluation of ventilation rates in schools

Abstract: The importance of maintaining adequate indoor air quality in schools is recognised as a contributing factor to pupils' learning performance. This paper describes a series of field measurements that investigating the ventilation rates in four recently built secondary schools in England. All schools were assessed for compliance with the recently adopted Building Bulletin 101, which defines the set of criteria in relation to the ventilation rates and indoor air quality in new school buildings. Using the obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 1 publication
3
13
0
2
Order By: Relevance
“…Another study indicates that classrooms should be designed capable of supplying enough fresh air, however, occupants should avail themselves of this capability [26]. This study suggests that good practice of ABs at the right time can prevent CO2 build-up and increase IAQ, as supported in [15,26,27,59,107,108]. A review of published studies spanning 1983-2013 suggests that behavioural changes have the potential to reduce indoor air pollution by 20%-98% in laboratory settings and 31%-94% in field settings [109].…”
Section: Co2 Levels and Occupant-related Factorsmentioning
confidence: 82%
“…Another study indicates that classrooms should be designed capable of supplying enough fresh air, however, occupants should avail themselves of this capability [26]. This study suggests that good practice of ABs at the right time can prevent CO2 build-up and increase IAQ, as supported in [15,26,27,59,107,108]. A review of published studies spanning 1983-2013 suggests that behavioural changes have the potential to reduce indoor air pollution by 20%-98% in laboratory settings and 31%-94% in field settings [109].…”
Section: Co2 Levels and Occupant-related Factorsmentioning
confidence: 82%
“…This was highlighted by Mateus et al [23] who presented a comparison of ventilation measurements and simulations in several classrooms. Mumovic et al [24] pointed on an interesting aspect of indoor air quality in school buildings-the interaction between the dynamic behavior of occupants and the building ventilation system. The paper by Kim and de-Dear [25] presents the similar study but from the point of view thermal comfort.…”
Section: Introductionmentioning
confidence: 99%
“…The present research acknowledges Post Occupancy Evaluation (POE) as the best tool to examine the safety performance in low cost housing. Many previous researches (Khalil & Nawawi, 2008;Mumovic et al 2009;Hassanain, 2007;Liu, 2003;Minami, 2007;Altas & Ozsoy, 1998;Collet da Graca et al, 2007;Gill et al, 2010;Amaratunga & Baldry, 1999;Foxall & Hackett, 1994;Goh & Ahmad, 2012) have showed significant results in optimizing the performance of building by applying POE as the research tool. Leaman et al (2010) described that buildings are self-evidently settings or 'contexts' for human activities.…”
Section: Introductionmentioning
confidence: 99%